Integrated strategy of LC-MS and network pharmacology for predicting active constituents and pharmacological mechanisms of Ranunculus japonicus Thunb. for treating rheumatoid arthritis. (10th May 2021) - Wang, Zhao-Yi; Chu, Fu-Hao; Gu, Nian-Nian; Wang, Yi; Feng, Dan; Zhao, Xia; Meng, Xue-Dan; Zhang, Wen-Ting; Li, Chao-Feng; Chen, Yang; Wei, Shuang-Shuang; Ma, Zhi-Qiang; et al.
Abstract: Ethnopharmacological relevance: Ranunculus japonicus Thunb. (short for R. japonicus ) is a topically applied herb with the activities of removing jaundice, nebula and edema, preventing malaria, stopping asthma, promoting diuresis and relieving pain. It was firstly recorded in Zhouhou Beiji Fang and has been used for the treatment of malaria, ulcers, carbuncle, jaundice, migraine, stomachache, toothache and arthritis for over 1800 years. Aim of the study: This study aimed to uncover the potentially effective components of R. japonicus and the pharmacological mechanisms against rheumatoid arthritis (RA) by combing LC-MS and network pharmacology. Materials and methods: Firstly, the chemical constituents of R. japonicus were qualitatively identified by UPLC-ESI-LTQ-Orbitrap MS. Then we performed target prediction by PharmMapper, protein-protein interaction (PPI) analysis via String, GO and KEGG pathway enrichment analysis by DAVID and constructed the compound-target-pathway network using Cytoscape. Thirdly, crucial compounds in the network were quantitatively analyzed to achieve quality control of R. japonicus. Finally, the pharmacological activities of R. japonicus and two potentially bioactive ingredients were validated in RA-FLSs (Rheumatoid Arthritis Fibroblast-like Synoviocytes) in vitro. Results: Overall fifty-four ingredients of R. japonicus were identified and forty-five components were firstly discovered in R. japonicus . Among them, twenty-seven validated compounds were predicted to act on twenty-five RA-related targets and they might exhibit therapeutic effects against RA via positive regulation of cell migration, etc. Nine potentially bioactive components of R. japonicus which played important roles in the compound-target-pathway network were simultaneously quantified by an optimized UPLC-ESI-Triple Quad method. In vitro, compared to control group, R. japonicus extract, berberine and yangonin significantly inhibited the migration capacity of RA-FLSs after 24 h treatment. Conclusion: This study clarified that R. japonic u s and the bioactive ingredients berberine and yangonin might exert therapeutic actions for RA via suppressing the aggressive phenotypes of RA-FLSs through combined LC-MS technology and network pharmacology tools for the first time. The present research provided deeper understanding into the chemical profiling, pharmacological activities and quality control of R. japonicus and offered reference for further scientific research and clinical use of R. japonicus in treating RA. Graphical abstract: Image 1